PAI Learning During the Covid-19 Pandemic at Madrasah Ibtidaiah: Pembelajaran PAI Pada Masa Pandemi Covid-19 di Madrasah Ibtidaiah - Zamhari, Muhammad Salsabila; Fauzi, Imam (Universitas Muhammadiyah Sidoarjo, 2021)
Currently, all nations around the world are being hit by a significant disaster caused by the Covid-19 infection. The Covid-19 infection finally had an impact on the world of coaching, including the strict learning of Islamic teachings. In a crisis like this, Islamic education and training actually plays an important role for students in dealing with the Covid-19 pandemic. Because basically the motivation behind learning Madrasah Ibtidaiyah is to expand students' beliefs, understanding, appreciation and practice of the religion of Islam with the aim that they become Muslim individuals who are pious and fearful of Allah SWT and have noble character near home, social life, and nation. The purpose of the problem formulation is to find out more about the Implementation of Learning and Learning Obstacles that occur in PAI learning during the Covid-19 pandemic. The method used is descriptive qualitative method using the method of observation, interviews and documentation. The analysis technique used in this research is data reduction, data presentation and conclusion drawing. The research results obtained are: 1). Implementation of online learning during the Covid-19 Pandemic Period at MI Hasyim Asy'ari Kejapanan. the implementation of learning during the covid-19 pandemic has been carried out quite well, it describes the status for implementing web-based learning. In the implementation of internet learning, educators have done illustration designs and have completed learning well, especially the use of learning media, methodologies, but web-based learning experiences obstacles in its implementation, unhealthy organizational conditions and difficulties in understanding students. teaching materials are tests in web-based learning. 2). Barriers to PAI Learning During the Covid-19 Pandemic at MI Hasyim Asy'ari Kejapanan. These barriers include: Unavailability of web organization, low dominance of innovation and lack of adequacy in teaching and learning.